Adaptive design strategies for buildings’ retrofit in response to climate change - Giulio Davino; Eduardo Bassolino (Agathón)
The urban temperature raising related to climate change on-going phenomenons as a consequence of greenhouse gas concentration’s increasing, the performance flaws of Italian construction, particularly of the one built between ‘70s and ‘90s, the technological progress of technical solutions and research in the field of architecture-related digital technology, have stimulated the development of a methodology based on computational design and data exchange IT tools for buildings’ energy simulation and the definition of interventions of energy and technology retrofit aimed towards adaption and mitigation according to climatic scenarios. This contribution is focused on the experimentation of a simulative approach, based on the use of parametric software for outlining interventions of energy and technology retrofit for buildings, through a methodology replicable for urban and building regeneration actions for mitigation and climate adaption.